Reforming Three Strikes' Excesses - Michael Vitiello (Washington University Law Quarterly, 2004)
The obvious solution to curb Three Strikes’ excesses is legislative reform of the Three Strikes law. This Article explores possible legislative reform. Proposition 184, the initiative creating the Three Strikes law, requires that any amendments to the law must be passed by a two-thirds majority of the legislature. Part II of this Article discusses the evidence that Three Strikes has failed in its promises to save money and lives and that the benefits that it delivers are unnecessarily expensive in light of limited benefits that it provides. Part III reviews the lack of success that Three Strikes defendants have had in the courts and in the legislature. Part IV addresses possible legislative reforms. It discusses the sentencing commission model. It then discusses why a narrow statute that would give content to “in furtherance of justice” would require only a simple majority in the legislature and would be desirable. Such a law would clarify a statute, § 1385, that the state supreme court has already found to be ambiguous, and it would not circumvent Three Strikes. Finally, Part V describes the proposed legislation.
Keywords: Guidelines; Sentences (Criminal procedure) – United States; Reforms – California; Sentences (Criminal procedure) – California; Prosecution – Decision making – California; Cruel and unusual punishment; Determinate sentences